The paradigm concept of Javanese’ Anak Polah Bapa Kepradhah in the story of Murwakala: Lévi-Strauss structuralism - Wardana, Sarwo Edi (Gelar: Jurnal Seni Budaya, 2023)
Indonesia harbors diverse oral traditions, with a particular focus on Javanese traditions. Studies on oral traditions, especially those related to geguritan (poems), stories, and songs, often lean towards aesthetic analyses. However, there remains untapped potential for exploration, such as the exploration of local cultural elements underlying the contradictions in folklore. This article aims to elucidate these contradictions and delineate the paradigmatic concept of “anak polah bapa kepradhah” within the narrative of “Murwakala.” Conducted as a descriptive-qualitative study, this research employs Lévi-Strauss structuralism as a framework for interpreting, mapping and attributing meaning to empirical paradigms embedded in societal concepts. The objective is to address the contradictions and logical patterns inherent in society. Data for this study are derived from the observation of Javanese oral traditions related to wong sukerta. These observations are then juxtaposed with the narrative of “Murwakala,” as presented in the wayang performance of the ruwatan tradition, with a specific focus on the Javanese “anak polah bapa kepradhah” concept/value. The depth of meaning is further explored through the use of tables and diagrams. From a Lévi-Straussian perspective, it can be concluded that “Murwakala” and its associated value concept serve as logical tools capable of mapping paradigms, deciphering empirical contradictions (related to family relationships and power), and representing these dynamics in the cultural products and thoughts of Javanese society, both historically and in the contemporary context.